The Principal's Leadership In Creating Quality Learning At Muhammadiyah 2 Vocational School, Yogyakarta - Muhamad Hani Yusuf (Mapendis: Jurnal Manajemen Pendidikan Islam, 2023)
Quality Learning at SMK Muhammadiyah 2 Yogyakarta. This study aims to determine how the principal's innovation in developing quality learning at SMK Muhammadiyah 2 Yogyakarta, and to determine how the picture of quality learning at SMK Muhammadiyah 2 Yogyakarta. This study uses a descriptive qualitative research method. Data collection techniques used are observation, interviews, documentation. The subjects of this study consisted of the Principal, the vice principal for curriculum, and teachers. The results of the study The Principal of SMK Muhammadiyah 2 Yogyakarta has made innovations in guiding teachers to create learning, which began with inviting resource persons to provide training to the board of teachers in the preparation of lesson plans by utilizing digital technology such as laptops and computers, and also conducting academic supervision to teachers by creating assessment instruments first. Innovation in developing conducive learning in creating quality learning, is done by utilizing supporting facilities such as computers, LCDs and Smart TVs in four classes at SMK Muhammadiyah 2 Yogyakarta. The picture of quality learning, can be seen in the preparation of lesson plans and then in the work groups in MGMP using digital technology.